Q-OPSEC: An architecture proposal for adaptive AI middleware for quantum cryptography - Noetzold, D.; Barbosa, J.; Santana, J.; Leithardt, V (Proceedings of International Conference on Electrical and Computer Engineering Researches (ICECER 2025), 2025)
Q-OPSEC is a proposed adaptive middleware architecture that integrates the strengths of the Oraculum and PRISEC models, now enhanced with quantum cryptography. Leveraging artificial intelligence-including supervised, unsupervised, and reinforcement learning-Q-OPSEC autonomously analyzes contextual information and dynamically selects cryptographic strategies. The architecture incorporates both classical and quantum-safe methods, such as Quantum Key Distribution (QKD) and post-quantum cryptographic (PQC) algorithms, to address current and emerging security threats. Designed as a plug-and-play solution for heterogeneous IoT and smart environments, Q-OPSEC adapts encryption strength and security policies in real time based on risk assessment and system context, aiming to fill critical gaps in context-aware and future-oriented data protection. Keywords—Artific